(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
The structural and magnetic properties modification in the bismuth substituted cobalt ferrite nanopowder with various molar concentrations of NaOH has been successfully synthesized by the coprecipitation method. The crystalline structure was measured using X-ray diffraction (XRD), bond groups, and absorption strength was measured by Fourier Transform Infrared spectroscopy (FTIR) studies, and then magnetic properties were measured using a Vibrating Scanning Magnetometer (VSM). The XRD measurement results confirmed that the whole samples of bismuth cobalt ferrite owing single phase of inverse spinel face cubic center (fcc) with space group Fd-3m were obtained for variations in molar concentration of NaOH. The FTIR measurements obtained that the absorption characteristic in the frequency band 400 - 750 cm-1 according to resonance at octahedral and tetrahedral sites of the occurrence metal oxide. The VSM measurement showed that the magnetic properties of bismuth substituted cobalt ferrite available to tune with modifying NaOH concentration in the co-precipitation procedure. Thus, the effect of increasing the concentration of NaOH into bismuth-substituted cobalt ferrite can change the characteristics of the cobalt ferrite such as lattice parameters, shifts in the absorption peaks of functional groups, and changes in magnetic saturation. The significance of this research is to know the exact concentration value of bismuth substituted cobalt ferrite to obtain the best characteristics.